Output error of converse piezoelectric fiber voltage sensor caused by optical fiber factors. (19th November 2019) - Yang, Han Rui; Qiao, Li; Xia, Lin Lin; Xu, Shi Bo; Guo, Yi Chang; Zhang, Yong Jie
In fiber voltage sensor, imperfect fiber splicing angle and length difference between the sensing fiber and the compensating fiber usually influence the system output performance. This article established the mathematical model of the system output error using the Jones matrix and analyzed the relationship between the system output error and the above two error factors, respectively. The results show that the angle error of 90° splice has a significant influence on the system output, and the tolerance of angle error varies with different test voltages. When the test voltage is higher than 6 kV, if the expected system error is less than 0.02%, the splicing angle error should be less than 0.15°. Additionally, the length difference also has a significant influence on the system output accuracy. The length difference between sensing fiber and compensating fiber should be less than 1 µm when the test voltage is 110 kV so that the system can meet the accuracy requirements of IEC 0.2s. This research provides a reference for the development of fiber voltage sensor based on the converse piezoelectric effect and also provides a basis for the design of intelligent power detection robot system.